WM1-2 SFX-01 after subarachnoid haemorrhage: protocol of a multi-centre, phase II, double-blinded, randomised controlled trial. Issue 3 (14th February 2019) - Zolnourian, A; Holton, P; Galea, I; Bulters, D
Abstract : Objectives: To assess the safety and efficacy of SFX-01 after subarachnoid haemorrhage. Design: SFX-01 is a synthetic agent that contains sulforaphane that has been shown to be neuroprotective in animal models of subarachnoid haemorrhage. This is a phase II double-bilinded, placebo-controlled randomised clinical trial. Subjects: Target of 90 patients with fisher 3 or 4 subarachnoid haemorrhage. Methods: Patients admitted to the three recruiting centres within 48 hours of ictus will be randomly allocated to placebo or SFX-01. The randomisation is stratified into WFNS 1–3 or 4–5. Participants will receive the trial medication in a capsule format twice-daily for 28 days. Patients will have transcranial dopplers (TCD) on alternate daily basis for at least 7 days. The maximum mean MCA flow velocity as well as safety are the two primary end-points. All patients will have paired blood and CSF taken at day 7 either through an LP or via EVD sampling. Follow-ups are performed at day 28, 3 months and 6 months which include safety bloods, functional questionnaires, mRS, GOSE and MRI. Results: 64 (71% of the target) patients have been enrolled. 35 patients have completed the study. Statistical analysis of the TCD data will be performed at the end of the trial. The mortality is at 9.5% (6). DSMB have met twice since the start of the trial and there have been no safety concerns. Conclusions: The trial is recruiting on the planned trajectory and at this rate we are projected to complete the trial by the end of the year.